Harmonization and Interpretation of the ifo Business Survey's Micro Data - Sebastian Link (Center for Economic Studies and ifo Institute (CESifo), 2018)
Every month, the ifo Business Survey (IBS) asks a representative set of 9000 German firms about their current and expected economic conditions. Thus, the micro data of the IBS are ideally suited to study various aspects of firm behavior. However, methodological heterogeneities between different subsets of the IBS have prevented joint analyses of firms in all main sectors of the economy. This paper expands the scope for economic research based on the IBS by presenting a harmonization procedure that overcomes these heterogeneities and that improves the possibility to merge firms to administrative industry-specific data at disaggregate levels. Moreover, the paper exploits the harmonized dataset to shed light on the interpretation of the most widely recognized variables in the IBS: firms' current business conditions and their expectations for the next six months. The results show that firms' assessments are strongly related to current and future levels in revenues and speak in favor of interpreting both questions as referring to the similar dimension of the same latent variable.
Keywords: C81; D22; D84; 330; Business Survey Data; interpretation of expectations and realizations